PENGARUH ROTASI KERJA, MUTASI KERJA DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BULUNGAN - Maryam Maryam; Syamsuddin Bidol; Ilham Safar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study was motivated by the suboptimal achievement of employee performance, the existing gap between performance targets and actual performance, and the need to evaluate human resource management policies, particularly those related to job rotation, job transfer, and job promotion. The study employed a quantitative approach using a survey method. The population consisted of 84 employees of the Department of Education and Culture of Bulungan Regency. Data were collected through questionnaires using a five-point Likert scale. The results indicate that human resource management policies, particularly job transfer and job promotion, have a positive contribution to improving employee performance. Conversely, the implementation of job rotation requires further evaluation to ensure greater alignment between employees' competencies, work experience, and organizational needs. Therefore, the Department of Education and Culture of Bulungan Regency is recommended to strengthen the implementation of the merit system by adopting objective, transparent, and competency-based mechanisms for job rotation, job transfer, and job promotion. These mechanisms should also be supported by competency mapping and continuous career development programs to enhance employee professionalism and improve the quality of public services.